2022
DOI: 10.1007/s00248-022-02004-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Microbial Pest Control Product Containing Bacillus thuringiensis on Brood Development and Gut Microbiota of Apis mellifera Worker Honey Bees

Abstract: To avoid potential adverse side effects of chemical plant protection products, microbial pest control products (MPCP) are commonly applied as biological alternatives. This study aimed to evaluate the biosafety of a MPCP with the active organism Bacillus thuringiensis ssp. aizawai (strain: ABTS-1857). An in-hive feeding experiment was performed under field-realistic conditions to examine the effect of B. thuringiensis (B. t.) on brood development and the bacterial abundance of the core gut microbiome (Bifidobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Research investigating the effect of microbial biopesticides on honey bee health is still developing (Borges et al 2021 ; Erler et al 2022 ), particularly their interaction with the gut microbiome (Steinigeweg et al 2023 ). In the present study, we reported for the first time how microbial combinations can affect honey bee survival under laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research investigating the effect of microbial biopesticides on honey bee health is still developing (Borges et al 2021 ; Erler et al 2022 ), particularly their interaction with the gut microbiome (Steinigeweg et al 2023 ). In the present study, we reported for the first time how microbial combinations can affect honey bee survival under laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…aizawai is an effective entomopathogen against lepidopteran larvae. However, its semi-specificity was indicated recently depending on the reported cross-effects across insect taxa and orders (e.g., Babin et al 2020 ; Nawrot-Esposito et al 2020 ; Steinigeweg et al 2021 , 2023 ; Tudoran et al 2020 ; van Frankenhuyzen 2017 ). This shows that target-specificity is not always as strong as expected.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that honey bees contaminated with typical agricultural pesticides are also at risk (Motta et al 2020;Steinigeweg et al 2023;Traynor et al 2016). A study investigating pesticide residues on migrated honey bee hives found 171 different pesticide residues present in the wax, bee bread and adult workers (Traynor et al 2016).…”
Section: Factors Negatively Affecting Honey Bee Gut Microbes and Poss...mentioning
confidence: 99%
“…These diseases are dangerous and affect both adult bees and their brood (Salmonellosis, Collibacilosis, Viral septicemia, American and European foulbrood, Aspergyllosis, etc.). For this reason, the health of the bee families and the efficiency of their activity depends on the veterinary sanitary measures undertaken by the beekeeper in close contact with veterinarians (3,4,5,6).…”
Section: Introductionmentioning
confidence: 99%